A rare case of acute destructive pancreatitis in a patient with chronic kidney disease on peritoneal dialysis: diagnostic and treatment challenges - V. A. Stepanov; O. N. Vetchinnikova (Вестник трансплантологии и искусственных органов)
Patients with chronic kidney disease are susceptible to developing acute pancreatitis. We present a rare clinical case of acute pancreatitis with the formation of pancreatic necrosis in a patient on peritoneal dialysis (PD), debuted with PD–associated peritonitis. On hospitalization, there were no diagnostic criteria for acute pancreatitis; treatment for dialysis peritonitis was ineffective. Repeated ultrasound examination revealed signs of diffuse changes in the pancreas and multi-chamber formation of the small pelvis. Refractory peritonitis, inadequate ultrafiltration, and unclear nature of formation in the pelvic were the grounds for diagnostic laparoscopy and removal of the peritoneal catheter. Abdominal inspection revealed spots of stearin necrosis over the entire surface of the peritoneum and the greater omentum; in the pelvis there were adhesions between the uterus and the rectum. Development of pancreonecrosis was confirmed by abdominal CT scan. Treatment of acute pancreatitis was without effect, type 2 myocardial infarction developed, and with increasing symptoms of multiple organ failure, death occurred.